Effects of Bacillus altitudinis inoculants on cigar tobacco leaf fermentation - Song, Wen; Chen, Xi; Yu, Jun; Qiao, Jingyu; Yang, Jinpeng; Chen, Xiong; Wang, Zhi (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Microbial succession and metabolic adjustment during cigar tobacco leaves (CTLs) fermentation are key factors to improve the quality and flavors of CTLs. However, the interactions in the above processes remain to be further elucidated.Methods: Bacillus altitudinis inoculants were added into the CTLs, metagenomics and metabolomics were used to analyze the inoculants effects on regulating microbial succession, metabolic shift, and aroma productions during the fermentation.The inoculants addition reinforced the CTLs macromolecule transformation, facilitated the aroma production efficiently, and the total aroma production were increased by 43% compared with the natural fermentation. The omics analysis showed that Staphylococcus was a main contributor to fatty acid degradation, inositol phosphate metabolism, energy supply (oxidative phosphorylation), nutrient transport (ABC transporter, PTS system), aroma production (terpenoid backbone biosynthesis, phenylalanine metabolism, degradation of aromatic compounds). Furthermore, Staphylococcus was positively correlated with TCA cycle intermediates (citric acid, fumaric acid, aconitic acid), cell wall componentspeptidoglycan intermediates (GlcNAc-1-P, UDP-GlcNAc), and phytic acid degradation products (inositol) etc. The characteristics collectively facilitated Staphylococcus to be the most dominant in the microbial community at the genus level during the microflora succession. Inoculants addition supplemented the nutritional components of the CTLs, enhanced the metabolic activity and diversity of the bacteria such as Corynebacterium, improved their competitive advantages in the microflora succession, and facilitated the richness of microbial communities.Additionally, a metabolic shift of nicotine degradation and NAD + anabolism from Staphylococcus to Corynebacterium in the inoculants addition fermentation was firstly observed. Meanwhile, the significantly correlative differential metabolites with Staphylococcus and Corynebacterium was a metabolic complementary, and thus forming a completely dynamic fermentation ecosystem. The results provided supports for CTLs fermentation optimization.